Experimental and theoretical investigation of cold-start exhaust behaviour under strategic engine control - Hoang, Dinh Long. (2008)
Cold-start emission control in the petrol engine is one of the main challenges for automotive engineers to meet ever-stringent emission standards. The main problem is the slow activation of the catalyst during the engine cold start phase. Although many approaches aimed at shortening catalyst lightoff time for cold-start emission reduction have been investigated, they are yet to be proven for practical applications. In this research project, fast catalyst lightoff was achieved by strategic controls of spark timing, idling engine speed and fuel-air mixture. Both experimental investigation and numerical simulation were performed to study cold start exhaust behaviour in the complete engine and exhaust system under strategic controls. The experimental work was conducted on a fully instrumented engine test bed with an electronically controlled FORD MVH-418 petrol engine. A programmable electronic engine management system (EMS) was successfully set up to accurately control ignition timing and lambda (equivalent air-fuel ratio) at the designed experimental conditions. Extensive experimental tests were carried out, in which the cylinder pressure, exhaust gas temperature, mass flow rate, and emission concentrations were measured. The results showed that, by properly controlling lambda and spark retard under a fixed engine idling speed, the exhaust gas temperature and mass flowrate can significantly increase and also engine-out emissions can be improved. The increase in exhaust energy speeded up the catalyst heating and shortened catalyst lightoff time. As a result, cold-start emissions at the tailpipe were significantly cut down. The engine warm-up was also improved.